Überlegungen zur theoretischen und praktischen Stärkung der Widerständigkeit von Sozialer Arbeit gegen die Therapeutisierung des Sozialen - Boris Friele (IUBH Internationale Hochschule, 2021)
– The phenomenon of the "therapeutisation of the social" is complex and directly affects the tasks and self-image of social work. This is first illustrated by the example of the debate on "AD(H)S". It is further assumed that everyday life and lifeworld orientation in the sense of Thiersch is part of professional identity and that this aspect of identity is undermined by therapeutisation processes. It is argued that a further theoretical profiling of the subject concept of everyday life and lifeworld orientation would increase the resistance of Thiersch's theoretical concept against unwanted appropriations, especially in connection with tendencies towards therapeutisation. Finally, it is discussed to what extent the study of social work could be made more sensitive to processes of therapeutisation and how social work competence could be strengthened in this context. The focus is particularly on the teaching and learning conditions of the dual study programme, which are seen as a special challenge for the teaching of socio-critical competence.
Keywords: 300; Therapeutisierung; Medikalisierung; Soziale Arbeit; ADHS; Lebensweltorientierung; duales Studium